EXPRESSION OF THE CYTOKINE GENES INDUCED BY HUMAN SERUM γ-GLOBULIN AND BY ITS METAL COMPLEXES WITH ZINC - S. B. Cheknev; M. V. Mezentseva; I. M. Shapoval; A. N. Narovlyansky (Медицинская иммунология, 2014)
Synthesis of mRNAs for the key immunoactive cytokines was studied in mononuclear cells (MNC) from human peripheral blood, using reverse transcription and polymerase chain reaction, after incubation of isolated cells with human serum γ-globulin, zinc ions, or zinc-γ-globulin metal complexes. A constitutive presence of interferon-α (IFNα) and interleukin-18 (IL-18) mRNA was shown in MNC of all of the subjects observed, whereas IFNγ, IL-4, or IL-8 mRNA synthesis was not detectable. Expression of IL-1β, IL-2, IL-6 и IL-10 was revealed in only a half of cases. It has been shown that pure γ-globulins did induce IFNγ gene expression and enhance transcriptional activity of IL-1β and IL-2 genes. Zinc cations did also promote transcription of IL-1β gene, along with reduced synthesis of IL-2 and IFNγ mRNA, compared to the γ-globulin. In presence of γ-globulin-zinc complexes, IL-1β mRNA was synthesized at the same level, as following induction with control γ-globulin, whereas IL-2 gene expression was reduced, and IFNγ mRNA synthesis was abolished. The results are discussed in terms of immune response polarization in presence of γ-globulins and their metal complexes with zinc.